EQ-5D visual analog scale and utility index values in individuals with diabetes and at risk for diabetes: Findings from the Study to Help Improve Early evaluation and management of risk factors Leading to Diabetes (SHIELD) - Fox Kathleen M; Grandy Susan (Health and Quality of Life Outcomes, 2008)
Abstract Background The EQ-5D was used to compare burden experienced by respondents with diabetes and those at risk for diabetes. Methods A survey including the EQ-5D was mailed to individuals with self-reported diabetes, as well as those without diabetes but with the following risk factors (RFs): (1) abdominal obesity, (2) body mass index ≥ 28 kg/m2, (3) dyslipidemia, (4) hypertension, and (5) cardiovascular disease. Non-diabetes respondents were combined into 0–2 RFs and 3–5 RFs. Mean EQ-5D scores were compared across groups using analysis of variance. Multivariable linear regression modeling identified factors affecting respondents' EQ-5D scores. Results Complete responses were available from >75% of each cohort. Mean EQ-5D index scores were significantly lower for respondents with type 2 diabetes and 3–5 RFs (0.778 and 0.792, respectively) than for those with 0–2 RFs (0.870, p < 0.001 for each); score for respondents with type 2 diabetes was also significantly lower than for those with 3–5 RFs (p < 0.001). Similar patterns were seen for visual analog scale (VAS). For both VAS and index scores, after adjusting for other characteristics, respondents reported decreasing EQ-5D scores as status moved from low to high risk (-6.49 for VAS score and -0.045 for index score) to a diagnosis of type 2 diabetes (-9.75 for VAS score and -0.054 for index score; p < 0.001 vs. 0–2 RFs for all). Conclusion High-risk and type 2 diabetes groups had similar EQ-5D scores, and both were substantially lower than in low-risk respondents.